The incidence of germinal centres in thymus glands of patients with congenital heart disease - Vetters, J. M. (1973)
The incidence of thymic germinal centres in normal individuals is disputed by various authors. The present study gives the results of a detailed histological assessment of 75 thymic biopsies obtained during operations to correct congenital heart lesions. Serial sectioning showed structures previously of disputed significance to be obliquely sectioned germinal centres. Comparison with the data of Hammar (1926) showed that there was some stress involution of the glands studied. Despite this 40% of the subjects had thymic germinal centres. Germinal centres were not detected in subjects under 4 years of age and there were insufficient subjects over 16 years of age to allow assessment of the frequency in adult thymus glands.